Mobile application for determining input level of fertilizer and detecting diseases in crops - Rashid, Tasneem Tazeen; Thuza; Hossain, Sazzad (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.